Analisis Hubungan Pertumbuhan Ekonomi Terhadap Ketimpangan Pembangunan antar Kecamatan di Kabupaten Ponorogo Tahun 2010-2014 - Setiawan, Joni, Yuni Prihadi Utomo, MM (2016)
This study will look at how much value inequality in Ponorogo and see patterns of inequality inside and analyze the correlation between inequality and economic growth in the region. Tests in this study using Williamson index analysis and entropy theil index and economic growth are then analyzed using Pearson analysis. In this study using secondary data from the Central Statistics Agency which is the statistical data from 2010-2014. Based on the results of analysis show that the analysis using Williamson index and Theil's entropy index can be known that inequality in the county Ponorogo is moderate, and it is known that from year to year has decreased 0.03383 and will possibly decline in the next year so that development be more evenly. While economic growth has increased from year to year despite the decline in inequality 2013.The value occurred in the year 2010 amounted to 0.4209 and the lowest inequality occurred in 2014 amounted to 0.2856. As for the highest economic growth in 2012 is 5.98% and the lowest occurred in 2013, namely 5.17% . Economic Growth ties are weak and not significantwith inequality index in the District Development Ponorogo. An area in Ponorogo district is 1371.78 and a population of 2010-2014 continues to increase annually by an average of 2,632 inhabitants. And population density of 656 persons / Km .